2017
DOI: 10.1038/ncomms14751
|View full text |Cite
|
Sign up to set email alerts
|

An NS-segment exonic splicing enhancer regulates influenza A virus replication in mammalian cells

Abstract: Influenza virus utilizes host splicing machinery to process viral mRNAs expressed from both M and NS segments. Through genetic analysis and functional characterization, we here show that the NS segment of H7N9 virus contains a unique G540A substitution, located within a previously undefined exonic splicing enhancer (ESE) motif present in the NEP mRNA of influenza A viruses. G540A supports virus replication in mammalian cells while retaining replication ability in avian cells. Host splicing regulator, SF2, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 60 publications
10
62
0
Order By: Relevance
“…Hence, the orchestrated synthesis of the viral proteome appears to be critically important for permissive infection. This supports the emerging view that modulation of viral protein synthesis underpins host adaptation 63 . Specifically, we find that the strain-specific differences in M1 protein synthesis critically depend on a conserved cis-regulatory element, which controls M-segment mRNA splicing.…”
Section: Discussionsupporting
confidence: 84%
“…Hence, the orchestrated synthesis of the viral proteome appears to be critically important for permissive infection. This supports the emerging view that modulation of viral protein synthesis underpins host adaptation 63 . Specifically, we find that the strain-specific differences in M1 protein synthesis critically depend on a conserved cis-regulatory element, which controls M-segment mRNA splicing.…”
Section: Discussionsupporting
confidence: 84%
“…Although no specific clinical sign and/or increase in the severity of respiratory disease in pigs was associated with infections with SwD group strains, it would be informative to further investigate potential group-specific phenotypic and/or functional characteristics. RNA secondary structure modification could indeed impact the splicing of NS mRNAs and subsequently regulate the expression of NS1 and NS2, two proteins that have important functions in the inhibition of host antiviral gene expression and/or in viral replication (37,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Huang et al. 's () study also has suggested that HP viruses originated mainly from the LP viruses of the Yangtze River Delta region that originated from a Wave 3‐like viruses and then obtained the four‐basic amino acid insertion in the Pearl River Delta. Guided by the ideas of Jin et al.…”
Section: Resultsmentioning
confidence: 99%
“…LP H7N9 viruses evolved into HP viruses by insertion of multibasic amino acids into the cleavage site (Huang et al., ), this multibasic cleavage site (MBCS) insertion can promote rapid cracking of HA0 (Munster et al., ), and high cleavability of the haemagglutinin glycoprotein was a necessary condition for lethal infection (Hatta, Gao, Halfmann, & Kawaoka, ). It has been confirmed that the basic amino acids around the HA cleavage site are the main factors determining the virulence of the influenza virus in chickens (Senne et al., ; Webster & Rott, ).…”
Section: Discussionmentioning
confidence: 99%